Integrative Model of Training and Motivation as a Strategy to Improve the Operational Performance of Brimob Personnel - Mustanir, Ahmad; Tahir, Rahmat; Nur , Muhammad (Journal of Indonesian Rural and Regional Government, 2025)
This study aims to analyze the influence of training and motivation on the performance of members of the South Sulawesi Police Pioneer Battalion A and formulate an integrative model that can be used as a strategy to improve operational performance. Using a quantitative approach with a correlational design, data was collected from 85 respondents through a Likert scale questionnaire. Data analysis was carried out by multiple linear regression using SPSS version 25. The results showed that training had a positive and significant effect on performance (β = 0.421; p < 0.05) and motivation had a greater influence on performance (β = 0.537; p < 0.05). Simultaneously, training and motivation explain 61% of the variation in member performance (R² = 0.610). These findings resulted in an Integrative Model of Training and Motivation as a strategic recommendation, which emphasizes the importance of a combination of improving technical competence through training and strengthening internal motivation through ongoing motivation programs. This model can be a reference in the formulation of human resource development policies within the Brimob.